1997
DOI: 10.2508/chikusan.68.1137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Whey Protein Concentrate on Postprandial Changes in Plasma Concentrations of Retinol and Triglyceride in Preruminant Calves

Abstract: Four Holstein male calves were used to study the effect of whey protein concentrate (WPC) on postprandial changes in plasma retinol and triglyceride concentrations. Suckling tests were conducted on the calves using Holstein cow whole milk mixed with Vitamin A acetate, with or without WPC, at weekly intervals from immediately after birth to 6 weeks of age. A catheter was inserted into a jugular vein and blood samples were taken from just until 8h after the feeding of the whole milk at 0800h. Plasma retinol and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In the second phase of the present study, the concentrations of plasma triglyceride in calves at 10 d of age were significantly higher in those given the β-lg diet than in the control calves during the period from 7 to 11 h after feeding. In a previous study, we clearly showed that preruminant calves fed whey protein concentrate (WPC) had significantly higher concentrations of plasma triglyceride than control calves (Kushibiki et al 1997). Because β-lg is a major protein in WPC, this response may be partly dependent upon the higher β-lg content of a milk diet (Kushibiki et al 1997).…”
Section: mentioning
confidence: 96%
See 1 more Smart Citation
“…In the second phase of the present study, the concentrations of plasma triglyceride in calves at 10 d of age were significantly higher in those given the β-lg diet than in the control calves during the period from 7 to 11 h after feeding. In a previous study, we clearly showed that preruminant calves fed whey protein concentrate (WPC) had significantly higher concentrations of plasma triglyceride than control calves (Kushibiki et al 1997). Because β-lg is a major protein in WPC, this response may be partly dependent upon the higher β-lg content of a milk diet (Kushibiki et al 1997).…”
Section: mentioning
confidence: 96%
“…In a previous study, we clearly showed that preruminant calves fed whey protein concentrate (WPC) had significantly higher concentrations of plasma triglyceride than control calves (Kushibiki et al 1997). Because β-lg is a major protein in WPC, this response may be partly dependent upon the higher β-lg content of a milk diet (Kushibiki et al 1997). On the other hand, β-lg of ruminants isolated from milk by non-denaturing methods contains several bound lipids, mainly triglyceride and long-chain fatty acids (Perez et al 1989).…”
Section: mentioning
confidence: 99%